The Role of Accounting in a Society: Only a techn(olog)ical solution for the problem of economic measurement or also a tool of social ideology? - Horvat, Robert; Korošec, Bojana (Naše gospodarstvo/Our economy, 2015)
The contribution juxtaposes the traditional neutralistic view on the role of accounting in a society as an activity of independent and unbiased measurement and presentation of real economic phenomena with the extended view on accounting as a socio-political practice and ideology. It also shows how the latter view impacts the understanding of the role of accounting and its reactions in light of the recent global financial crisis.